PENINGKATAN PERTUMBUHAN IKAN SIDAT (ANGUILLA BICOLOR) DENGAN PEMANFAATAN PEDICLE KERANG LENTERA SEBAGAI BAHAN PAKAN - Jandri Fan Ht. Saragi; Ria Retno (Media Bina Ilmiah, 2022)
The market demand for eel is very high. In January – August 2011 the export volume of eel decreased by 39.1% from the same period in 2010. The decline in exports was the impact of constraints on eel cultivation, namely the long growth of fish. A good feed for eels is fresh meat feed from fish, crustaceans, and shellfish. The composition of the feed has an impact on the high cost of feed production. Brachiopoda lingulata are often found in the waters of Batubara Regency as "tail clams". Lantern shells are waste that can be used as fish feed ingredients, besides having high nutrition, Brachiopoda lingulata also have bioactive substances in their bodies. This study aimed to examine the effect of using Brachiopoda lingulata pedicles on eel growth based on survival response, specific growth rate, feed conversion ratio, protein efficiency ratio and protein retention of eel (A. bicolor) stadia elver. The method used is an experimental method where this method is to see the causal relationship between the dependent variable and the independent variable. Experimental research consisted of 5 treatments with 3 replications, carried out on a laboratory scale to minimize external influences. Data analysis with quantitative methods. The test was analyzed using a Completely Randomized Design (CRD), the analysis tested the effect of treatment, followed by the Smallest Significant Difference (BNT) test. The addition of the best Brachiopoda lingulata pedicle flour is 2% of fish meal protein substitution seen from the survival response, namely 95.6%, specific growth rate 0.95%/BW/day, feed conversion ratio 2.64 and protein efficiency ratio 0.83.